Genetic diversity and population structure of Ethiopian Sweet Sorghum [Sorghum bicolor (L.) Moench] germplasms using SSR markers - Tefera Habtegiorgis Teklewold; Tsegaye Getahun Bogale; Demsachew Guadie Tseganeh; Muluken Enyew Birara; Tileye Feyissa Senbeta (PLoS ONE, 2025)
Sweet sorghum is a cereal crop in the grass family belonging to the genus Sorghum bicolor L. Moench. It is known in its sugary juice that is accumulated in its stalk and efficient C4 photosynthetic pathway. Only few molecular genetic diversity studies of Ethiopian sweet sorghum have been carried out. Understanding the genetic diversity of plants is the basis for genetic improvement, effective conservation and efficient utilization of genetic resources. Therefore, the objective of this study was to evaluate the genetic diversity and population structure of Ethiopian sweet sorghum genotypes collected from major growing areas of Ethiopia. In the present study, thirteen SSR markers produced a total of 136 alleles across all the 91 sweet sorghum accessions with an average of 10.46 alleles per marker. The major allele frequency per marker ranged from 0.16 to 0.41 with an average of 0.25. The number of alleles per marker ranged from 6 to 15. The mean PIC value was 0.80. The pair-wise genetic differentiation among the five studied sweet sorghum populations ranged from 0.07 to 0.19. The highest Fst (0.19) and the lowest Fst (0.07) population differentiation were observed between sweet sorghum population of South Wollo and Oromia Liyu Zone, and North Shewa and East Gojam sweet sorghum populations, respectively. The analysis of gene flow across populations showed that the highest gene flow was recorded between North Shewa and East Gojam (2.879), whereas the least gene flow was observed between South Wollo and Oromia Liyu Zone (0.618). The analysis of molecular variance revealed that 16% variation was observed among populations and 84% variation has been observed within populations. Meanwhile, the STRUCTURE and UPGMA methods of clustering suggested that the sampled sweet sorghum populations were clustered into two main groups (K =  2). This comprehensive study of genetic diversity and population structure of sweet sorghum (Sorghum bicolor) in Ethiopia suggests that future sweet sorghum improvement and utilization strategies should take the magnitude and pattern of genetic diversity into consideration.